1995
DOI: 10.1111/j.1528-1157.1995.tb01622.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and Treatment of eizures in Children with Acute Lymphoblastic Leukemia

Abstract: We reviewed the records of 127 consecutive pediatric patients with acute lymphoblastic leukemia (ALL) to determine the incidence, timing, etiologies, and recurrence rate of seizures in this population. Patients with ALL and seizures were identified retrospectively by review of the records of all pediatric ALL patients who were diagnosed and treated during the years 1983 through March 1993 in a large tertiary-care hospital. Seventeen patients (13%) developed one or more seizures. In 16 patients, seizures occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 10 publications
1
49
2
Order By: Relevance
“…Such events are triggered by acute treatment toxicity, which might be related to chemotherapeutic neurotoxicity, cranial radiation, metabolic complications, cerebral hemorrhage, CNS infection, cerebral vascular disorders, and leukemic infiltration. 2,3 Mesial temporal lobe epilepsy with hippocampal sclerosis (MTLE-HS) is characterized by intractable epilepsy with complex partial seizures (CPSs) of temporal origin and temporal sclerosis and represents the final common pathway of several processes. 4 Early detection of MTLE-HS is important, because these children are likely candidates for brain surgery and have an excellent chance of a subsequent normal life.…”
mentioning
confidence: 99%
“…Such events are triggered by acute treatment toxicity, which might be related to chemotherapeutic neurotoxicity, cranial radiation, metabolic complications, cerebral hemorrhage, CNS infection, cerebral vascular disorders, and leukemic infiltration. 2,3 Mesial temporal lobe epilepsy with hippocampal sclerosis (MTLE-HS) is characterized by intractable epilepsy with complex partial seizures (CPSs) of temporal origin and temporal sclerosis and represents the final common pathway of several processes. 4 Early detection of MTLE-HS is important, because these children are likely candidates for brain surgery and have an excellent chance of a subsequent normal life.…”
mentioning
confidence: 99%
“…It is commonly used to treat many pediatric cancers, including ALL, lymphoma, and bone or soft tissue sarcomas. A pediatric ALL study incorporated a retrospective review of 127 children and demonstrated a 13% incidence rate (n=17) of seizures in this population [6]. Sixteen of these patients experienced seizures after receiving intrathecal methotrexate or subcutaneous L-asparaginase.…”
Section: Seizuresmentioning
confidence: 99%
“…We have demonstrated that hepatocellular Rfc1-mediated MTX influx is significantly reduced after treatment with a clinically relevant concentration of the antiepileptic drug (AED) PB or CBZ as a result of post-transcriptional down-regulation of the carrier protein (Halwachs et al, 2007). In childhood ALL, seizures represent a frequent clinical manifestation of MTX neurotoxicity particularly related to intrathecal MTX (Maytal et al, 1995). Besides, seizures due to metabolic disorders, cerebral infarction, or CNS infection have been observed (Maytal et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In childhood ALL, seizures represent a frequent clinical manifestation of MTX neurotoxicity particularly related to intrathecal MTX (Maytal et al, 1995). Besides, seizures due to metabolic disorders, cerebral infarction, or CNS infection have been observed (Maytal et al, 1995). As in these patients, comedication with AEDs is regularly required (Tibussek et al, 2006), we examined the contribution of Rfc1 to MTX transport at the blood-CSF barrier and investigated the effect of AEDs on Rfc1 uptake activity on the functional, transcriptional, and posttranscriptional level using the rat CP-like in vitro model Z310 (Zheng and Zhao, 2002;Shi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%